REKAYASA SEMEN KOMPOSIT LIMBAH SERUTAN BAMBU SEBAGAI BAHAN ALTERNATIF PERKERASAN JALAN (PAVING BLOCK) - Eratodi IGLB; Ariawan Putu (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2017)
Rigid concrete pavement is a pavement needed on a special typical load area and alsoneeded a low maintenance. Problems arise when there is limited sand material available and the costis also expensive. Solutions developed in this research apply cement composite materials mixedwith bamboo shavings waste hence building materials that are lightweight, environmentally friendlyand has the character of a concrete class were obtained. This cement composite material hasadvantages in utilization of bamboo shaving waste and therefore reduces environmental pollution.The purpose of this research were to engineer alternative paving materials in the form of pavingblock made of bamboo shaving waste mixture composite cement. This research has obtained theoptimum physical and mechanical properties of the composite cement material and paving block at aspecific mixture composition. The physical and mechanical properties that are tested on pavingblock samples had five compositions variation of cement (S): sand (P): and bamboo fibre (B) of1:6:0; 1:4.5:1.5; 1:3:3; 1:1.5:4.5; and 1:0:6 respectively with catalyst of CaCl2 as much as 3 %volume. The results have showed that the physical properties of the concrete slab have optimumwater content of 16.67 % at variation of 1:4.5:1.5 and optimum mass density of 0.550 kg/m3 atvariation of 1:3:3. The mechanical properties test of the concrete slab have showed meancompressive strength of 19.8 MPa, mean Modulus of Rupture (MOR) of 16.40 MPa and meanModulus of Elasticity (MOE) of 11,500 MPa respectively at variation of 1:4.5:1.5. Optimum wearresistance value at variation of 1:3:3 on average were 0.698 mm/min. The physical properties testresults for the paving block had mean water content of 6.77 % and mean mass density of 0.761kg/m3 respectively at variation of 1:3:3. The value of mean MOR, mean MOE and mean wearresistance were 27.16 MPa, 11,583 MPa and 0.864 mm/min respectively for variation of 1:3:3. Abstrak: Perkerasan jalan beton merupakan perkerasan yang dibutuhkan pada area bertipikal bebankhusus dan low maintenance. Permasalahan penggunaan beton muncul ketika ketersediaan bahanpasir terbatas dan harganya mahal. Solusi yang dikembangkan dalam penelitian ini menerapkanbahan komposit semen dengan limbah serutan bambu sehingga diperoleh bahan bangunan yangringan, ramah lingkungan dan memiliki karakter sekelas beton. Bahan semen komposit ini memilikikeuntungan dalam pendayagunaan limbah serutan bambu sehingga ikut mengurangi pencemaranlingkungan. Tujuan penelitian ini adalah membuat rekayasa komponen bahan alternatif perkerasanjalan dalam bentuk paving block dari semen komposit campuran bahan limbah serutan bambu.Penelitian ini mendapatkan sifat fisika dan mekanika optimum bahan semen komposit dan pavingblock pada komposisi campuran tertentu. Sifat fisika dan mekanika yang diuji pada benda uji pavingblock dengan 5 variasi perbandingan semen(S): pasir(P): dan serat bambu(B), yaitu 1:6:0; 1:4,5:1,5;1:3:3; 1:1,5:4,5 dan 1:0:6 dengan katalis CaCl2 sebanyak 3% volume. Hasilnya menunjukkan sifatfisika papan semen memiliki nilai optimum kadar air 16,67% pada variasi 1:4,5:1,5 dan berat jenisoptimum 0,550 kg/m3 pada variasi 1:3:3. Hasil uji sifat mekanika papan semen yaitu kuat tekan rataratasebesar 19,8 MPa, Modulus of Repture (MOR) rata-rata sebesar 16,40 MPa dan Modulus ofElasticity (MOE) rata-rata sebesar 11.500 MPa pada variasi 1:4,5:1,5. Nilai ketahanan aus optimumpada variasi 1:3:3 rata-rata sebesar 0,698 mm/menit. Hasil uji sifat fisika paving block dengan kadarair rata-rata 6,77% dan kerapatan rata-rata 0,761 kg/m3 pada variasi 1:3:3. Nilai rata-rata MOR,MOE dan ketahanan aus masing-masing sebesar 27,16 MPa, 11.583 MPa, dan 0,864 mm/menit padavariasi 1:3:3.Kata kunci : Serutan bambu, semen komposit, paving block.